2015
DOI: 10.2319/040215-219.1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of self-perceived pain, discomfort, and impairment of jaw function in children undergoing orthodontic treatment with fixed or removable appliances

Abstract: Objective: To compare patients' perceptions of fixed and removable appliance therapy for correction of anterior crossbite in the mixed dentition, with special reference to perceived pain, discomfort, and impairment of jaw function. Materials and Methods: Sixty-two patients with anterior crossbite and functional shift were recruited consecutively and randomized for treatment with fixed appliances (brackets and archwires) or removable appliances (acrylic plates and protruding springs). A questionnaire, previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 17 publications
4
28
0
Order By: Relevance
“…[2223] This is due to the fact that removable appliances reduce and change the intraoral space, thus impeding the tongue from articulating certain speech sounds. In addition, speech problems in the removable appliance group can also be a contributing factor to the negative effect on schoolwork and leisure activities reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2223] This is due to the fact that removable appliances reduce and change the intraoral space, thus impeding the tongue from articulating certain speech sounds. In addition, speech problems in the removable appliance group can also be a contributing factor to the negative effect on schoolwork and leisure activities reported.…”
Section: Discussionmentioning
confidence: 99%
“…[1718192021222324] Kurtz reported that females can express more the characteristics of the experiences they go through better than males. [2526] This study showed that the female group OHRQoL in the fixed appliances group showed less irritability and physical limitation in comparison to male patients and that there weas a noticeable improvement as the treatment reached T4.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that removable appliances reduce and change the intraoral space, thus precluding the tongue from articulating certain speech sounds. In addition speech problems in the removable appliance group can also be a contributing factor to the negative effect on schoolwork and leisure activities reported [20]. It is therefore not surprising that in our study the Twin block group demonstrated poorer quality of life at the beginning of the treatment since the appliance is bulky and hinders patients' speech.…”
Section: Discussionmentioning
confidence: 44%
“…The fixed appliance group experienced more pain than the Twin Block group when eating, since the latter were asked to remove the appliance during meals. Authors reported that patients with removable appliances group experienced more issues with speech during treatment and had negative effects on schoolwork and leisure activities [20]. This is due to the fact that removable appliances reduce and change the intraoral space, thus precluding the tongue from articulating certain speech sounds.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is dependent upon such factors as age, gender, stress, individual pain threshold, cultural differences, in addition to the amount of force applied. Researchers have already reported that pain associated with orthodontic treatment has a potential impact on daily life, mainly as psychological distress . Orthodontists often suggest to parents to eventually give children, in the first day after visit, drugs for pain that might be caused by the appliances used for orthodontic and orthopaedic treatment .…”
Section: Introductionmentioning
confidence: 99%